Talins and Cancer - Mohamed S Attia Gaballah; Zeinab A Hassan; Mahmoud Youns (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2017)
Talin is a large cytoskeletal adaptor protein that is an important component of focal adhesion complexes of adherent cells. It was originally identified as a component of focal adhesions and ruffling membranes of fibroblasts. It was the first cytoplasmic protein partner of integrins to be identified. Many studies proved that talin connects the intracellular actin cytoskeleton with the extracellular environment through interactions with integral membrane proteins in the dynamic focal adhesions. The modular structure of talin is responsible for its ability to serve as a linker protein. It was thought that animal cells contained only one talin. However, studies have been identified a second talin (Talin-2) in vertebrates. Talin-1 levels are very low in brain and striated muscle, but high in kidney, liver, spleen, stomach, lung, and rat vascular smooth muscle cells. Talin-2 levels are high in brain and striated muscle. The variable expression of Talin-2 in these differentiated cells reflects that these proteins have different roles, which would be reflected in different properties of each protein. Moreover, Talins may be a good target for treatment of certain types of cancers. Talins levels are altered in various types of cancer indicating its possible use as cancer biomarker.